A randomized controlled trial of a supportive expressive group intervention for women with a family history of breast cancer. Issue 11 (17th July 2018) - Esplen, Mary Jane; Leszcz, Molyn; Hunter, Jonathan; Wong, Jiahui; Leung, Yvonne W.; Toner, Brenda; Messner, Sandra; Glendon, Gord; Stuckless, Noreen; Butler, Catherine
Abstract: Objective: Women with a family history of breast cancer (BC) often overestimate their BC risk. Heightened psychological distress may interfere with risk comprehension and screening adherence. The primary purpose of this study was to test the efficacy of a 12‐week manual‐based supportive‐expressive (SE) group intervention for this population. Methods: Using a randomized control trial design, this study compared two interventions: a standard risk‐counseling arm (RC) compared with that plus SE group intervention. The primary study outcome was BC anxiety. Secondary outcomes included psychosocial functioning, risk comprehension, BC knowledge, and screening behaviors. Results: A total of 161 women with a family history of BC were randomized into SE ( N  = 108) or RC ( N  = 53). Participants in both study arms significantly improved on measures of BC anxiety, psychosocial functioning, risk comprehension, and BC knowledge, with no statistical difference between study arms. Benefits were sustained at 1 year. BC screening rates were high in both arms at baseline and follow‐up. Conclusions: SE group therapy as an added intervention to the risk counseling was well‐received, however, did not demonstrate superiority to RC alone. Future studies on treatment matching are needed to further our understanding of interventions that can support women with a family history of BC to work through residual issues, including loss and grief.